Battery composite electrode plate and method for manufacturing the same

CN116581235BActive Publication Date: 2026-10-09SINOWATT DONGGUAN
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310614851.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-26
Publication Date
2026-10-09
Estimated Expiration
2043-05-26

AI Technical Summary

Technical Problem

[0004]本发明的目的在于提供电池复合极片及其制备方法,旨在解决现有技术中,二次电池正负极片之间的界面阻抗大的问题

Benefits of technology

[0017] Compared with existing technologies, the method for preparing the battery composite electrode provided by this invention involves sequentially stacking a negative electrode coating, a porous copper foil, a solid electrolyte layer, a porous aluminum foil, and a positive electrode coating to form a continuous, integrated battery composite electrode. This integrated structure of positive and negative electrodes is not only simple to manufacture and reduces battery manufacturing costs, but also effectively reduces the contact resistance between the positive and negative electrodes, significantly improving the utilization rate of the battery's internal space and thus enhancing the overall performance of the battery. Specifically, by coating a solid electrolyte layer on the porous copper foil, replacing the separator in existing technologies, the battery safety performance is improved; compared to the method of winding the positive and negative electrodes with the separator, the interfacial resistance between the positive and negative electrodes is effectively reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116581235B_ABST
    Figure CN116581235B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of secondary battery pole piece preparation, and discloses a preparation method of a battery composite pole piece, which comprises the following steps: S10, selecting a porous copper foil for a battery, coating a solid-state electrolyte on one side surface of the porous copper foil to form a solid-state electrolyte layer; S20, coating or plating a porous aluminum foil on the surface of the solid-state electrolyte layer; S30, coating a positive electrode material on the surface of the porous aluminum foil to form a positive electrode coating layer, and coating a negative electrode material on the other side surface of the porous copper foil to form a negative electrode coating layer; and finally obtaining the battery composite pole piece. The negative electrode coating layer, the porous copper foil, the solid-state electrolyte layer, the porous aluminum foil and the positive electrode coating layer are sequentially stacked to form a through-type integrated battery composite pole piece. The integrated structure of the positive electrode and the negative electrode is not only simple to manufacture, but also can reduce the manufacturing cost of the battery, effectively reduce the contact resistance between the positive electrode and the negative electrode, greatly improve the internal space utilization of the battery, and thus improve the comprehensive performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of secondary battery electrode preparation, and more specifically, to battery composite electrodes and their preparation methods. Background Technology

[0002] In the design of secondary batteries, the separator and current collectors (including copper foil and aluminum foil) are important components that directly affect the battery's manufacturing process, electrical performance, and safety performance. Copper foil, as a common current collector for the negative electrode, has high ductility and tensile strength, and is typically used with a thickness of 5–10 μm. Aluminum foil, as a current collector for the positive electrode, has lower ductility and tensile strength than copper foil, and is typically used with a thickness of 10–20 μm. The common thickness of the separator is 10–20 μm.

[0003] Currently, commercially available rechargeable batteries are assembled by stacking or winding positive and negative electrodes with a separator, then injecting electrolyte and encapsulating them. A separator is placed between the positive and negative electrodes to prevent direct contact between the positive and negative terminals, which could cause a short circuit. However, this internal battery design is not only relatively complex to assemble and manufacture, making it difficult to process various ultra-thin or irregularly shaped batteries, but also results in high interfacial impedance between the positive and negative electrodes and the separator due to the large gap between them, leading to poor cycle performance, low battery space utilization, and low energy density. Summary of the Invention

[0004] The purpose of this invention is to provide a composite electrode for batteries and a method for preparing the same, aiming to solve the problem of high interfacial impedance between the positive and negative electrodes of secondary batteries in the prior art.

[0005] This invention is achieved through a method for preparing a battery composite electrode, comprising the following steps:

[0006] S10: Select a porous copper foil for the battery, and coat a solid electrolyte onto one side surface of the porous copper foil to form a solid electrolyte layer;

[0007] S20: A porous aluminum foil is coated or plated on the surface of the solid electrolyte layer;

[0008] S30: Coating the surface of the porous aluminum foil with a positive electrode material to form a positive electrode coating; coating the other side of the porous copper foil with a negative electrode material to form a negative electrode coating; finally obtaining the battery composite electrode sheet.

[0009] Optionally, after steps S10 to S20, a porous composite current collector is formed.

[0010] Optionally, the material of the solid electrolyte layer is selected from one or more of lithium lanthanum titanium oxide, lithium lanthanum zirconium oxide, lithium lanthanum zirconium titanium oxide, lithium titanium aluminum phosphate, and lithium germanium aluminum phosphate.

[0011] Optionally, the thickness of the solid electrolyte layer is 3 to 20 μm.

[0012] Optionally, the porous copper foil and the porous aluminum foil have a thickness of 5 to 20 μm, a pore size of 1 to 100 μm, and a porosity of 20 to 80%.

[0013] Optionally, the thickness of the positive electrode coating and the negative electrode coating is 50-100 μm.

[0014] Optionally, the porous copper foil has a first through hole, and the porous aluminum foil has a second through hole, with the first through hole and the second through hole corresponding one-to-one.

[0015] Optionally, the first through hole and the second through hole are circular in shape.

[0016] A battery composite electrode sheet, wherein the battery composite electrode sheet prepared by the above-described method comprises a negative electrode coating, a porous copper foil, a solid electrolyte layer, a porous aluminum foil, and a positive electrode coating stacked sequentially to form an integrated structure.

[0017] Compared with existing technologies, the method for preparing the battery composite electrode provided by this invention involves sequentially stacking a negative electrode coating, a porous copper foil, a solid electrolyte layer, a porous aluminum foil, and a positive electrode coating to form a continuous, integrated battery composite electrode. This integrated structure of positive and negative electrodes is not only simple to manufacture and reduces battery manufacturing costs, but also effectively reduces the contact resistance between the positive and negative electrodes, significantly improving the utilization rate of the battery's internal space and thus enhancing the overall performance of the battery. Specifically, by coating a solid electrolyte layer on the porous copper foil, replacing the separator in existing technologies, the battery safety performance is improved; compared to the method of winding the positive and negative electrodes with the separator, the interfacial resistance between the positive and negative electrodes is effectively reduced. Attached Figure Description

[0018] Figure 1 This is a cross-sectional schematic diagram of the porous composite current collector in the method for preparing composite electrode sheets for batteries provided by the present invention;

[0019] Figure 2 This is a cross-sectional schematic diagram of the battery composite electrode obtained by the method for preparing the battery composite electrode provided by the present invention.

[0020] Explanation of reference numerals in the attached figures:

[0021] 1-Porous composite current collector, 11-Porous copper foil, 12-Solid electrolyte layer, 13-Porous aluminum foil;

[0022] 2- Battery composite electrode, 21- Negative electrode coating, 23- Positive electrode coating. Detailed Implementation

[0023] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0024] The implementation of the present invention will be described in detail below with reference to specific embodiments.

[0025] In the accompanying drawings of this embodiment, the same or similar reference numerals correspond to the same or similar components. In the description of this invention, it should be understood that if terms such as "upper," "lower," "left," and "right" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the drawings, they are only for the convenience of describing this invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, the terms used to describe positional relationships in the drawings are only for illustrative purposes and should not be construed as limiting this invention. For those skilled in the art, the specific meaning of the above terms can be understood according to the specific circumstances.

[0026] Reference Figure 1-2 The image shows a preferred embodiment of the present invention.

[0027] The method for preparing a battery composite electrode includes the following steps:

[0028] S10: Select a porous copper foil 11 for the battery, and coat a solid electrolyte on one side surface of the porous copper foil 11 to form a solid electrolyte layer 12.

[0029] S20: Coating or depositing porous aluminum foil 13 on the surface of the solid electrolyte layer 12;

[0030] S30: A positive electrode material is coated on the surface of the porous aluminum foil 13 to form a positive electrode coating 23; a negative electrode material is coated on the other side of the porous copper foil 11 to form a negative electrode coating 21; finally, the battery composite electrode 2 is obtained.

[0031] The method for preparing the battery composite electrode provided in this embodiment involves sequentially stacking a negative electrode coating 21, a porous copper foil 11, a solid electrolyte layer 12, a porous aluminum foil 13, and a positive electrode coating 23 to form a continuous, integrated battery composite electrode 2. This integrated structure combining the positive and negative electrodes is not only simple to manufacture and reduces battery manufacturing costs, but also effectively reduces the contact resistance between the positive and negative electrodes, significantly improving the utilization rate of the battery's internal space and thus enhancing the overall performance of the battery. Specifically, coating the porous copper foil 11 with a solid electrolyte layer replaces the separator in existing technologies, resulting in higher battery safety performance; compared to the method of winding the positive and negative electrodes with the separator, it effectively reduces the interfacial resistance between the positive and negative electrodes.

[0032] In this embodiment, after steps S10 to S20, a porous composite current collector 1 is formed. Then, a positive electrode material is coated on the surface of the porous aluminum foil 13 of the porous composite current collector 1, and a negative electrode material is coated on the surface of the porous copper foil 11 of the porous composite current collector 1, thereby forming a battery composite electrode 2.

[0033] The porous copper foil 11 has multiple first through holes arranged in an array. The porous aluminum foil 13 has multiple second through holes arranged in an array. Preferably, the first and second through holes are arranged in a one-to-one correspondence. This one-to-one correspondence arrangement of the through holes facilitates the transport of lithium ions and reduces the internal resistance of the battery.

[0034] The shape of the first through hole and the second through hole can be one or more of the following: circular, square, rhomboid, and rectangular.

[0035] Specifically, the material of the solid electrolyte layer 12 is selected from one or more of lithium lanthanum titanium oxide (LLTO), lithium lanthanum zirconium oxide (LLZO), lithium lanthanum zirconium titanium oxide (LLZTO), lithium titanium aluminum phosphate (LATP), and lithium germanium aluminum phosphate (LAGP).

[0036] Typical inorganic ceramic oxide solid electrolytes include perovskite type, garnet type, LISICON type, and NASICON type.

[0037] Among them, the representative material of perovskite-type solid electrolytes is LLTO (lithium lanthanum titanium oxide / lithium lanthanum titanate, Li...). 0.33 La 0.56 TiO3), and the representative material of garnet-type solid electrolytes is LLZO (lithium lanthanum zirconium oxide / lithium lanthanum zirconate, Li7La3Zr2O). 12 The representative material for NASICON (sodium superionic conductor) type solid electrolytes is LATP (lithium aluminum titanium phosphate, Li). 1.3 Al 0.3 Ti 1.7 (PO4)3).

[0038] Lithium lanthanum titanium oxide (LLTO) can achieve a bulk conductivity of 1 x 10⁻⁶ at room temperature. -3 The conductivity of LLTO is S / cm, but its grain boundary conductivity is two orders of magnitude smaller than its bulk conductivity. The bottleneck effect results in a low total conductivity of LLTO, which needs to be improved by doping and other means.

[0039] The ionic conductivity of lithium lanthanum zirconium oxide (LLZO) at 25 °C is 3 × 10⁻⁶. -4 With a resistance of S / cm, the grain boundary resistance accounts for less than 50% of the total resistance. The overall ionic conductivity of LLZO is on the same order of magnitude as the intracrystalline ionic conductivity, ensuring its high overall ionic conductivity as a solid electrolyte.

[0040] Lithium aluminum titanium phosphate (LATP) and lithium aluminum germanium phosphate (LAGP) have ionic conductivity as high as 10 at room temperature. -4 S / cm. LATP is chemically stable in humidified air or carbon dioxide, has high ionic conductivity and a wide electrochemical window, making it suitable as a solid electrolyte material for high-voltage solid-state batteries.

[0041] Specifically, the thickness of the solid electrolyte layer 12 is 3–20 μm.

[0042] Optionally, the porous copper foil 11 and porous aluminum foil 13 have a thickness of 5 to 20 μm, a pore size of 1 to 100 μm, and a porosity of 20 to 80%.

[0043] Optionally, the thickness of the positive electrode coating 23 and the negative electrode coating 21 is 50-100 μm.

[0044] In another embodiment, the method for preparing the battery composite electrode includes the following steps:

[0045] S10: Select a porous copper foil 11 for the battery, and coat a solid electrolyte on one side surface of the porous copper foil 11 to form a solid electrolyte layer 12.

[0046] S20: An adhesive is coated on the surface of the porous aluminum foil 13 to form an adhesive layer, and the porous aluminum foil 13 is bonded to the solid electrolyte layer 12 through the adhesive layer.

[0047] S30: A positive electrode material is coated on the surface of the porous aluminum foil 13 to form a positive electrode coating 23; a negative electrode material is coated on the other side of the porous copper foil 11 to form a negative electrode coating 21; finally, the battery composite electrode 2 is obtained.

[0048] The adhesive layer is a polyurethane adhesive with a thickness of 1–3 μm.

[0049] Specifically, the material of the solid electrolyte layer 12 is selected from one or more of lithium lanthanum titanium oxide (LLTO), lithium lanthanum zirconium oxide (LLZO), lithium lanthanum zirconium titanium oxide (LLZTO), lithium titanium aluminum phosphate (LATP), and lithium germanium aluminum phosphate (LAGP).

[0050] Specifically, the thickness of the solid electrolyte layer 12 is 3–20 μm.

[0051] Optionally, the porous copper foil 11 and porous aluminum foil 13 have a thickness of 5 to 20 μm, a pore size of 1 to 100 μm, and a porosity of 20 to 80%.

[0052] Optionally, the thickness of the positive electrode coating 23 and the negative electrode coating 21 is 50-100 μm.

[0053] In another embodiment, the method for preparing the battery composite electrode includes the following steps:

[0054] S10: Select a porous copper foil 11 for the battery, and coat an adhesive on one side surface of the porous copper foil 11 to form an adhesive layer;

[0055] S20: An adhesive is coated on the surface of the porous aluminum foil 13 to form an adhesive layer;

[0056] S30: The porous copper foil 11 and porous aluminum foil 13 in S10 and S20 are respectively pressed and bonded to the front and back sides of the solid electrolyte layer 12 through an adhesive layer to form a porous composite current collector 1;

[0057] S40: A positive electrode material is coated on the surface of the porous aluminum foil 13 of the porous composite current collector 1 to form a positive electrode coating 23; a negative electrode material is coated on the other side of the porous copper foil 11 of the porous composite current collector 1 to form a negative electrode coating 21; finally, the battery composite electrode 2 is obtained.

[0058] The adhesive layer is a polyurethane adhesive with a thickness of 1–3 μm.

[0059] Specifically, the material of the solid electrolyte layer 12 is selected from one or more of lithium lanthanum titanium oxide (LLTO), lithium lanthanum zirconium oxide (LLZO), lithium lanthanum zirconium titanium oxide (LLZTO), lithium titanium aluminum phosphate (LATP), and lithium germanium aluminum phosphate (LAGP).

[0060] Specifically, the thickness of the solid electrolyte layer 12 is 3–20 μm.

[0061] Optionally, the porous copper foil 11 and porous aluminum foil 13 have a thickness of 5 to 20 μm, a pore size of 1 to 100 μm, and a porosity of 20 to 80%.

[0062] Optionally, the thickness of the positive electrode coating 23 and the negative electrode coating 21 is 50-100 μm.

[0063] A battery composite electrode 2, prepared by the above-described method, comprises a negative electrode coating 21, a porous copper foil 11, a solid electrolyte layer 12, a porous aluminum foil 13, and a positive electrode coating 23 sequentially stacked to form an integrated structure. This battery composite electrode 2 can be directly applied to ultra-thin batteries in a flat manner without the need for additional separators, electronic insulation layers, etc.

[0064] In the following specific embodiment 1,

[0065] The battery composite electrode 2 includes a negative electrode coating 21, a porous copper foil 11, a solid electrolyte layer 12, a porous aluminum foil 13, and a positive electrode coating 23 stacked sequentially, wherein the porous copper foil 11, the solid electrolyte layer 12, and the porous aluminum foil 13 form a porous composite current collector 1. The positive electrode coating 23 is coated on the surface of the porous aluminum foil 13 of the porous composite current collector 1, and the negative electrode coating 21 is coated on the surface of the porous copper foil 11 of the porous composite current collector 1.

[0066] The production steps are as follows:

[0067] S10: Select a porous copper foil 11 for the battery, with a thickness of 5μm, a pore size of 50μm, and a porosity of 40%. Coat one side surface of the porous copper foil 11 with a solid electrolyte to form a solid electrolyte layer 12, the thickness of which is 4μm.

[0068] S20: A porous aluminum foil 13 is coated or plated on the surface of the solid electrolyte layer 12, with a thickness of 5 μm, a pore size of 50 μm, and a porosity of 40%.

[0069] S30: A positive electrode material is coated on the surface of the porous aluminum foil 13 to form a positive electrode coating 23 with a thickness of 50 μm; a negative electrode material is coated on the other side of the porous copper foil 11 to form a negative electrode coating 21 with a thickness of 50 μm; finally, the battery composite electrode 2 is obtained.

[0070] In the following specific embodiment 2,

[0071] The battery composite electrode 2 includes a negative electrode coating 21, a porous copper foil 11, a solid electrolyte layer 12, a porous aluminum foil 13, and a positive electrode coating 23 stacked sequentially, wherein the porous copper foil 11, the solid electrolyte layer 12, and the porous aluminum foil 13 form a porous composite current collector 1. The positive electrode coating 23 is coated on the surface of the porous aluminum foil 13 of the porous composite current collector 1, and the negative electrode coating 21 is coated on the surface of the porous copper foil 11 of the porous composite current collector 1.

[0072] The production steps are as follows:

[0073] S10: Select a porous copper foil 11 for the battery, with a thickness of 5μm, a pore size of 50μm, and a porosity of 40%. Coat one side surface of the porous copper foil 11 with a solid electrolyte to form a solid electrolyte layer 12, the thickness of which is 4μm.

[0074] S20: An adhesive is coated on the surface of the porous aluminum foil 13 to form an adhesive layer with a thickness of 1 μm. The porous aluminum foil 13 is bonded to the solid electrolyte layer 12 through the adhesive layer. The porous aluminum foil 13 has a thickness of 5 μm, a pore size of 50 μm, and a porosity of 40%.

[0075] S30: A positive electrode material is coated on the surface of the porous aluminum foil 13 to form a positive electrode coating 23 with a thickness of 50 μm; a negative electrode material is coated on the other side of the porous copper foil 11 to form a negative electrode coating 21 with a thickness of 50 μm; finally, the battery composite electrode 2 is obtained.

[0076] In the following specific embodiment 3,

[0077] The battery composite electrode 2 includes a negative electrode coating 21, a porous copper foil 11, a solid electrolyte layer 12, a porous aluminum foil 13, and a positive electrode coating 23 stacked sequentially, wherein the porous copper foil 11, the solid electrolyte layer 12, and the porous aluminum foil 13 form a porous composite current collector 1. The positive electrode coating 23 is coated on the surface of the porous aluminum foil 13 of the porous composite current collector 1, and the negative electrode coating 21 is coated on the surface of the porous copper foil 11 of the porous composite current collector 1.

[0078] The production steps are as follows:

[0079] S10: Select a porous copper foil 11 for the battery, with a thickness of 5μm, a pore size of 50μm, and a porosity of 40%. Coat one side surface of the porous copper foil 11 with an adhesive to form an adhesive layer with a thickness of 1μm;

[0080] S20: An adhesive is coated on the surface of the porous aluminum foil 13 to form an adhesive layer with a thickness of 1 μm. The porous aluminum foil 13 has a thickness of 5 μm, a pore size of 50 μm, and a porosity of 40%.

[0081] S30: The porous copper foil 11 and porous aluminum foil 13 in S10 and S20 are respectively pressed and bonded to the front and back sides of the solid electrolyte layer 12 through an adhesive layer to form a porous composite current collector 1. The thickness of the solid electrolyte layer 12 is 5μm.

[0082] S40: A positive electrode material is coated on the surface of the porous aluminum foil 13 of the porous composite current collector 1 to form a positive electrode coating 23 with a thickness of 50 μm; a negative electrode material is coated on the other side of the porous copper foil 11 of the porous composite current collector 1 to form a negative electrode coating 21 with a thickness of 50 μm; finally, the battery composite electrode 2 is obtained.

[0083] The present invention provides a method for preparing a battery composite electrode and the resulting battery composite electrode. The method involves sequentially stacking a negative electrode coating 21, a porous copper foil 11, a solid electrolyte layer 12, a porous aluminum foil 13, and a positive electrode coating 23 to form a continuous, integrated battery composite electrode 2. This integrated structure of positive and negative electrodes is not only simple to manufacture and reduces battery manufacturing costs, but also effectively reduces the contact resistance between the positive and negative electrodes, significantly improving the utilization rate of the battery's internal space and thus enhancing the overall performance of the battery. Specifically, coating the porous copper foil 11 with a solid electrolyte layer replaces the separator in existing technologies, resulting in higher battery safety performance. Compared to the method of winding the positive and negative electrodes with the separator, this method effectively reduces the interfacial impedance between the positive and negative electrodes. This battery composite electrode 2 can be directly applied to ultra-thin batteries in a flat state without the need for additional separators, electronic insulation layers, etc.

[0084] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a composite electrode for a battery, characterized in that, Includes the following steps: S10: Select a porous copper foil for the battery, and coat a solid electrolyte onto one side surface of the porous copper foil to form a solid electrolyte layer; S20: A porous aluminum foil is coated or plated on the surface of the solid electrolyte layer; S30: A positive electrode material is coated on the surface of the porous aluminum foil to form a positive electrode coating; a negative electrode material is coated on the other side of the porous copper foil to form a negative electrode coating; finally, the battery composite electrode sheet is obtained. After steps S10 to S20, a porous composite current collector is formed; The porous copper foil and the porous aluminum foil have a thickness of 5~20μm, a pore size of 1~100μm, and a porosity of 20~80%.

2. The method for preparing the battery composite electrode as described in claim 1, characterized in that, The material of the solid electrolyte layer is selected from one or more of lithium lanthanum titanium oxide, lithium lanthanum zirconium oxide, lithium lanthanum zirconium titanium oxide, lithium titanium aluminum phosphate, and lithium germanium aluminum phosphate.

3. The method for preparing the battery composite electrode as described in claim 2, characterized in that, The thickness of the solid electrolyte layer is 3–20 μm.

4. The method for preparing the battery composite electrode as described in claim 1, characterized in that, The thickness of the positive electrode coating and the negative electrode coating is 50-100 μm.

5. The method for preparing the battery composite electrode as described in claim 1, characterized in that, The porous copper foil has a first through hole, and the porous aluminum foil has a second through hole, with the first through hole and the second through hole corresponding one-to-one.

6. The method for preparing the battery composite electrode as described in claim 5, characterized in that, The first through hole and the second through hole are circular in shape.

7. A composite electrode for a battery, characterized in that, The battery composite electrode obtained by the method for preparing the battery composite electrode according to any one of claims 1-6, wherein the negative electrode coating, the porous copper foil, the solid electrolyte layer, the porous aluminum foil, and the positive electrode coating are sequentially stacked to form an integrated structure.

Citation Information

Patent Citations

  • Lithium ion battery structure

    CN110071294A

  • All-solid-state battery with low interface resistance and preparation method of all-solid-state battery

    CN111525181A

  • Secondary battery and preparation method therefor

    WO2017190367A1